FORECASTING PLANNING AND PROCUREMENT STRATEGY OF RAW MATERIAL USING MATERIAL REQUIREMENTS PLANNING METHODE - Imam Taifur, Salam; Tukhas Shilul Imaroh (Dinasti Publisher, 2020)
The research was conducted in the building material manufacturing industry. Research focus onplanning and controlling raw fiber roof fiber cement raw material using the Material Requirement Planning method. Problems that occur because of fluctuations in stock. By evaluating the planning process, calculating raw material requirements and then reviewing the most efficient Lotsizing techniques between Fixed Order Quantity, Economic Order Quantity, Lot for Lot, Period Order Quantity. Besides that, a strategy is also studied so that MRP can be applied. From the application of the lot sizing technique, the most efficient lotting method is obtained from the Lot for Lot method at a cost of Rp. 5.29 billion. The application of MRP also has an impact on improving inventory performance, changes in minimum and maximum stock changes that are adjusted to production activities. Efficient purchase costs from total raw material needs with an average value of Rp 8.33 billion.